Assessment of Distal Motor Latency of the Femoral Nerve in Clinically Healthy Adult Dogs - Mortari, Ana C.; Lima, Julia L.A.; Almeida, Ricardo M.; Rahal, Sheila C. [UNESP] (Elsevier, 2019)
This study aimed to evaluate femoral nerve latency time recorded from both vastus lateralis and vastus medialis muscles, in clinically healthy dogs. Eighteen adult dogs were distributed into 2 distinct body mass ranges (Group 1: 1-4.1 kg, n= 9; Group 2: 4.2-13 kg, n= 8), according to the median body mass (4.1 kg). Distal motor latencies for the femoral nerve were obtained in right- and left hind limbs. Platinum surface electrodes were used to record the latency of femoral nerve from the vastus lateralis muscle, whereas coaxial needle electrodes were used to record the latency from the vastus medialis muscle. The distal motor nerve latencies were 1.52 ± .23 milliseconds and 1.69 ± .42 milliseconds, respectively, for vastus lateralis and vastus medialis muscles. There were no significant differences of distal motor nerve latencies between vastus lateralis and vastus medialis muscles. Hind limb length of Group 1 was significant shorter than Group 2. There were no significant differences of latencies between Groups 1 and 2. No significant correlations were observed between latency and body mass, and between latency and hind limb length for dogs of both groups. In conclusion, the femoral motor latency measurement was easy to obtain and may supply additional data in the examination of diseases that affect the hind limbs. Latency values of vastus lateralis longer than 1.52 ± .23 milliseconds in small/medium-sized breeds may be considered as suggestive of a femoral neuropathy.
Keywords: dog; femoral nerve; motor nerve conduction; peripheral nerve